Perceived Stress and Quality of Life Among Caregivers of Individuals with Schizophrenia: A Cross-Sectional Correlational Analysis in Indonesia - Tri Sumarsih; Norkiah Binti Arsat; Baidi Bin Baddiri; Meidiana Dwidiyanti (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Family caregivers of individuals with schizophrenia frequently endure chronic stress, adversely affecting their quality of life (QoL). This study addresses a significant research gap by exploring the relationship between stress and QoL in a low-resource context in Indonesia. Methods: A cross-sectional correlational study was conducted involving 104 family caregivers in Kebumen, Indonesia. Data were gathered using the Perceived Stress Scale (PSS-10) and WHOQOL-BREF, followed by analysis through chi-square tests and multiple logistic regression to identify QoL predictors. Results: The majority of caregivers reported moderate stress (57.7%) and good QoL (67.3%). A notable inverse correlation was identified between stress levels and QoL (p = 0.001). Logistic regression indicated that moderate-to-high stress levels (OR = 0.29; 95% CI: 0.11–0.72; p = 0.008), caregiving duration exceeding five years (OR = 2.74; 95% CI: 1.24–6.09; p = 0.013), and low income under Rp500,000 (OR = 0.31; 95% CI: 0.12–0.79; p = 0.011) significantly predicted QoL. Conclusion: Perceived stress is a crucial factor influencing the well-being of caregivers for individuals with schizophrenia. Enhancing community-based mental health initiatives, including stress assessments and socioeconomic support, could improve caregiver QoL in rural Indonesian settings.